2017
DOI: 10.1044/2017_jslhr-h-16-0154
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Training for Adults Who Have Hearing Loss: A Comparison of Spaced Versus Massed Practice Schedules

Abstract: The lack of spacing effect in otherwise effective auditory training suggests that perceptual learning may be subject to different influences than are other types of learning, such as vocabulary learning. Hence, clinicians might have latitude in recommending training schedules to accommodate patients' schedules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
3
17
0
1
Order By: Relevance
“…If more training does not change the nature of learning, what does it do? One option is that multi-session training could provide further opportunities for learning to stabilize and consolidate without changing the overall nature of learning [38,59,60]. This is consistent with the outcomes of both labbased [37,61,62] and rehabilitation-oriented [22,60] studies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…If more training does not change the nature of learning, what does it do? One option is that multi-session training could provide further opportunities for learning to stabilize and consolidate without changing the overall nature of learning [38,59,60]. This is consistent with the outcomes of both labbased [37,61,62] and rehabilitation-oriented [22,60] studies.…”
Section: Discussionsupporting
confidence: 64%
“…One option is that multi-session training could provide further opportunities for learning to stabilize and consolidate without changing the overall nature of learning [38,59,60]. This is consistent with the outcomes of both labbased [37,61,62] and rehabilitation-oriented [22,60] studies. For example, in speech category learning, listeners accumulate information about the acoustic characteristics of the talker over time [61,63], thus additional experience with a talker is likely to result in additional gains.…”
Section: Discussionsupporting
confidence: 64%
“…Эффективность дистанционных и массовых слуховых тренировок показана в работе Tye-Murray N, Spehar B, Barcroft J, et al [8]. Результаты проведенного исследования подтверждают равную эффективность слуховых тренировок для пациентов с ХСНТ, использующих СА, как дистанционных, так и массовых.…”
Section: результаты и их обсуждениеunclassified
“…In addition, improvements from training can be specific to trained stimuli, and may or may not depend on the length of the training course, and on other factors (see reviews by Lawrence et al, 2018 ; Bieber and Gordon-Salant, 2021 ). Tye-Murray et al (2017) examined the benefits of auditory training in 47 experienced HA users, who were divided into two training groups, that differed in the time course of training. One group received training in the lab twice a week for 10 weeks, and the other group received more intensive training where they had to train 5 days a week for 2 weeks in the lab.…”
Section: Introductionmentioning
confidence: 99%
“…As has been seen in previous studies, the period needed to observe improvements is unknown and because recent studies have shown that short exercises or short exposure to a listening task may show improvements similar to long-term training sessions (e.g., Tye-Murray et al, 2017 ), exercises in the current design were divided into blocks and sessions and were administered in a period of 3 weeks. The exercises included tasks in quiet and noisy listening conditions, and tasks of detection, discrimination, identification and comprehension, taking into consideration the model of Erber and Hirsh (1978) .…”
Section: Introductionmentioning
confidence: 99%